Philippe Borgueaud, La Mère des Dieux. De Cybèle à la Vierge Marie, París, Seuil, 1996, 266 pp. ISBN 2-02-010903-4 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Philippe Borgueaud, La Mère des Dieux. De Cybèle à la Vierge Marie, París, Seuil, 1996, 266 pp. ISBN 2-02-010903-4